Assessment of the Fetal Heart During Routine Obstetrical Screening, a Standardized Method. (September 2016) - Scott, Ted; Jones, Judy; Swan, Hans
Assessment of the fetal heart during routine obstetrical screening remains a challenge for sonographers and physicians. Reliance on still images and nonstandard methods of acquiring images and assessing the fetal heart contribute to the relatively low rate of identification of congenital heart disease (CHD). A standardized assessment of the fetal heart using two cine-loop sweeps has been shown to address some of these challenges. Image acquisition using two cine-loop sweeps combined with a standardized five-step assessment is proposed to address the limitations of the nonstandard approach in place at most screening centers today.